Analisis Pelaksanaan Trias Usaha Kesehatan Sekolah (UKS) dan Perilaku Hidup Bersih dan Sehat (PHBS) di SLB C di Bantul - Rahmah Widyaningrum; Mei Neni Sitaresmi; Lely Lusmilasari (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Evaluation of triage programs school health unit and clean and health living behavior in school for children with special educational needs BantulPurposeThis study aimed to get an overview of school health unit and implementation of clean and health living behavior in school for children with special educational needs. MethodsThis research used qualitative methods with a case study approach. Participants of the study included the principal, the teacher, students and public health center staff, the senior managers of the school, and the Yogyakarta provincial youth and sports education department. Qualitative data were obtained through in-depth interviews, observations, and documentation studies. ResultsThe implementation of trias school health unit program was in the good category. Some clean and health living indicators were still in low category. The obstacles of the school health unit and clean and health living behavior program implementation were limited understanding of students, low coverage of teacher and school training, economic conditions and parental attitudes, school readiness, and involvement of relevant agencies. Factors affecting school health unit implementation included curriculum, school organization, and partnership. ConclusionThe implementation of school health unit and clean and health can be enhanced through partnership optimization with community health centers, related offices, non-governmental organizations, and education and health universities.